Experimental and Theoretical Investigation of Supercritical Processes: Kinetics of Phase Transitions in Binary “2-Propanol—CO2” System - Ekaterina Suslova; Maria Mochalova; Artem Lebedev (Computation, 2023)
Studies of phase transition kinetics are important for such supercritical processes as supercritical drying, adsorption, micronization, etc. In supercritical technologies, “organic solvent—CO2” systems are often formed, the properties of which strongly depend on the system parameters. In this article, the kinetic curves of phase transitions in the “2-propanol—CO2” system were investigated experimentally and theoretically. Experimental studies were carried out in a 250 mL high-pressure apparatus at temperatures of 313 and 333 K and pressures of 6.3 and 7.8 MPa with and without the addition of alginate porous gel. Theoretical studies were carried out using the mass transfer equation, the Peng-Robinson equation of state, and the Van der Waals mixing rules, with Python being used for the calculations. The mass transfer coefficients and equilibrium concentrations of CO2 in the liquid phase were determined using the BFGS optimization method.